2019
DOI: 10.1097/j.pain.0000000000001611
|View full text |Cite
|
Sign up to set email alerts
|

NLRP2 inflammasome in dorsal root ganglion as a novel molecular platform that produces inflammatory pain hypersensitivity

Abstract: Inflammatory pain hypersensitivity is associated with activation of primary afferent neurons. This study investigated the existence of the inflammasome in dorsal root ganglion (DRG) and the functional significance in the development of inflammatory pain hypersensitivity. Tissue inflammation was induced in male C57BL/6 mice with complete Freund's adjuvant (CFA) or ceramide injection into the hind paw. Behavioral testing was performed to investigate inflammation-induced pain hypersensitivity. Ipsilateral L5 DRGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 36 publications
0
43
0
Order By: Relevance
“…Moreover, ceramideinduced thermal hyperalgesia is also known to be mediated by nuclear factor kappa-lightchain-enhancer of activated B cells (NF-κB)-and p38 mitogen-activated protein kinase (MAPK)-dependent cyclooxygenase-2 (COX-2) induction and increased prostaglandin E2 (PGE 2 ) production [49] ( Figure 2). A recent study also demonstrated the involvement of nodlike receptor family, pyrin domain containing 2 (NLRP2) signaling in ceramide-induced hypersensitivity [50]: intraplantar injection of ceramide in mice increases the expression of NLRP2 and inflammatory cytokine IL-1β in DRG neurons.…”
Section: S1p Axis In Peripheral Sensitizationmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, ceramideinduced thermal hyperalgesia is also known to be mediated by nuclear factor kappa-lightchain-enhancer of activated B cells (NF-κB)-and p38 mitogen-activated protein kinase (MAPK)-dependent cyclooxygenase-2 (COX-2) induction and increased prostaglandin E2 (PGE 2 ) production [49] ( Figure 2). A recent study also demonstrated the involvement of nodlike receptor family, pyrin domain containing 2 (NLRP2) signaling in ceramide-induced hypersensitivity [50]: intraplantar injection of ceramide in mice increases the expression of NLRP2 and inflammatory cytokine IL-1β in DRG neurons.…”
Section: S1p Axis In Peripheral Sensitizationmentioning
confidence: 94%
“…[36] CLCN3 and CLCN5 mediate excitatory Clcurrents activated by S1P/S1PR3 in mouse sensory neurons 2018 [71] S1P-to-S1PR3 signaling mediates pain behaviors in mice through the activation of TRPV1 in sensory neurons 2018 [61] Sexual dysmorphic responses are observed with bortezomib. Unlike paclitaxel and oxaliplatin, S1PR1-based therapies do not block bortezomib-induced neuropathic pain in female rats and mice 2019 [111] Ceramide-induced pain behaviors in mice involve NLRP2 inflammasome activation in the DRG 2019 [50] Activation of S1PR1 in spinal astrocytes, following intrathecal injection of SEW2871, leads to NLRP3 inflammasome activation, IL-1β production, and pain behaviors in mice and rats 2019 [81] Functional and competitive S1PR1 antagonists block traumatic nerve injury-induced neuropathic pain in mice and rats. S1PR1 expressed on astrocytes is identified as a target for therapeutic intervention with S1PR1 antagonists 2019 [84] S1PR2 activation in spinal cord attenuates neuropathic pain and neuroinflammation in a model of traumatic nerve injury in rats 2019 [91] Clinical trials for proof of concept in patients with breast cancer have begun with fingolimod to explore efficacy in preventing and/or treating chemo-induced neuropathic pain (NCTID: NCT03941743; NCT03943498) 2019 i FTY720 ameliorates spinal cord injury induced-neuropathic pain in rats by dampening neuroinflammation and inhibiting glial scar formation 2020 [97] Role for S1PR1 in opioid-mediated adverse events is identified.…”
Section: Disclaimer Statementmentioning
confidence: 99%
“…NLRP2 can form an inflammasome with ASC and caspase-1 to provide maturation of pro-inflamammatory IL-1β and IL-18 [ 103 , 104 ]. Notably, Minkiewicz et al (2013) showed that NLRP2 was activated in astrocytes by ATP via the P2X7 receptor and the pannexin 1 channel, similar to mechanisms reported for NLRP3.…”
Section: Atp-dependency For the Assembly And Activation Of Selectementioning
confidence: 99%
“…Overall, these data suggest astrocytic NLRP2 is likely an important component of inflammatory response in the central nervous system (CNS) [ 103 ]. Another study further solidified the role of NLRP2 in CNS inflammation using a mouse model [ 104 ]. NLRP2 was significantly upregulated in dorsal root ganglion as were, although to a lesser extent, NLRP3 and NLRP1.…”
Section: Atp-dependency For the Assembly And Activation Of Selectementioning
confidence: 99%
“…TNF-α was expressed in the majority of voltage-gated sodium channel (Nav) 1.3-positive or Nav1.8-positive neurons and up-regulated the expression of Nav1.3 and Nav1.8 in DRG neurons following peripheral nerve injury [23]. Cleaved IL-1β expression was signi cantly increased in small-sized DRG neurons after CFA injection into the hind paw [31]. IL-6 was up-regulated in the ipsilateral L4 and L5 DRG neurons and in the bilateral lumbar spinal cord following L5-ventral root transaction and contributed to the development of neuropathic pain [25].…”
Section: A and B)mentioning
confidence: 99%